Conceptual design for state control of a prosthesis finger / Abdul Halim Abdul Kadir @ Mat Isa - Abdul Kadir @ Mat Isa, Abdul Halim (2010)
A prosthesis works as an aid to help recover some of the lost functions of an amputated organic limb. This study focuses on the conceptual mechatronic design of a laboratory finger prosthesis which resembles both the key physical features and the grasping functionality of a middle adult finger by means of a new specification techniques, i.e. Systems Modeling Language (SysML). SysML is a general-purpose graphical modeling language that supports the analysis, specification, design, verification and validation of complex systems. These systems may include hardware, software, data, personnel, procedures, facilities and other elements of manmade and natural systems. SysML can represent systems, components and other entities such as structural composition, constraints on the physical and performance properties. The conceptual design of the prosthetic finger which is geared towards four essential characteristics: (i) anthropomorphically accurate size, (ii) kinematically accurate motion, (iii) hybrid actuation mechanism, and (iv) tactile sensory feedback. The list below shows the type of the diagrams which has been made using the SysML program: I. Use case diagram II. Block definition diagram III. State machine diagram IV. Activity diagram V. Requirement diagram